College degree completion for GEAR UP students placed at risk - Sanchez, Jafeth E.; Usinger, Janet (Frontiers in Education, 2025)
The purpose of this study was to examine academic and personal variables as predictors of degree completion within 150% of the normal time for students participating in the federally funded Gaining Early Awareness and Readiness for Undergraduate Programs (GEAR UP) grant. The study aimed to identify which factors most strongly influenced college completion among students traditionally placed at risk. Academic and personal variables analyzed included 12th-grade GPA, 7th-grade college aspirations, cumulative GEAR UP program service hours, gender, middle school setting, and race/ethnicity. A binary logistic regression analysis was conducted to determine the extent to which these variables predicted timely college completion. The resulting model identified 12th-grade GPA and cumulative GEAR UP program service hours as significant predictors of degree completion within 150% of normal time. Students with higher GPAs and greater participation in GEAR UP programming were more likely to graduate on time. Findings suggest that sustained academic performance and engagement in GEAR UP services contribute meaningfully to college completion among students from historically underrepresented groups. Implications for program design and recommendations for future research are discussed.